Correspondence of Florence O'Donoghue with Gerard Anthony Hayes-McCoy - O'Donoghue, Florence, 1895-1967; Hayes-McCoy, Gerard Anthony, 1911-1975 (1955)
Letters relate mainly to attempts to verify the authorship of Patrick Pearse's 'valedictory letter' of 24th April 1916. Also includes an envelope addressed to Diarmuid Lynch.
Keywords: Lynch, Diarmuid, -- 1878-1950; Pearse, Padraic, -- 1879-1916.; Ireland -- History -- 1910-1921; Ireland -- History -- Autonomy and independence movements; Ireland -- History -- 1922-